Professional Learning Opportunities in a Practice-Based Teacher Education Programme about the Concept of Function - Ribeiro, Alessandro Jacques (2019)
This article aims to identify professional learning opportunities (PLO) experienced by mathematics teachers during an in-service course regarding their mathematical and didactical knowledge on the concept of function. The conceptual framework distinguishes between mathematical and didactical knowledge and characterises teacher learning and professional learning tasks. The research methodology is qualitative, using participant observation with audio and video recording and document collection. The results show that the professional learning tasks proposed enabled to identify PLO regarding mathematical knowledge of function, involving different ways of representing this concept by means of numeric tables and algebraic notation. Regarding didactical knowledge, there were also PLO supporting reflection about difficulties that the students find with the concept of function and about teaching resources and strategies to overcome those difficulties.